Predictors of treatment efficacy and ALT non‐normalization with sofosbuvir/ribavirin therapy for patients with hepatitis C virus genotype 2. Issue 9 (23rd May 2017) - Watanabe, Takao; Tokumoto, Yoshio; Joko, Kouji; Michitaka, Kojiro; Horiike, Norio; Tanaka, Yoshinori; Tada, Fujimasa; Kisaka, Yoshiyasu; Nakanishi, Seiji; Nonaka, Takashi; Yamauchi, Kazuhiko; Hirooka, Masashi; et al.
Abstract : The tolerability and efficacy of sofosbuvir and ribavirin in patients infected with hepatitis C virus (HCV) genotype 2 were investigated under actual clinical conditions. A total of 208 patients with chronic HCV genotype 2 infection were treated with sofosbuvir 400 mg and ribavirin (weight‐based dosing) for 12 weeks. Treatment discontinuation and sustained virological response 12 (SVR12) were evaluated. Moreover, factors associated with SVR12, hemoglobin decreasing to less than 10 g/dL during treatment, and alanine aminotransferase (ALT) non‐normalization after treatment were evaluated. In all patients, SVR12 responses were 96.1% (200/208). About 6 of 8 patients (3.8%) who did not achieve SVR12 were re‐treatment patients, and eight patients who did not achieve SVR all had liver cirrhosis. Multivariate analysis also identified body mass index (OR = 0.79; P  < 0.001), platelet count (OR = 0.88; P  = 0.003), and estimated glomerular filtration rate (eGFR) (OR = 0.96; P  = 0.007) as independent contributing factors associated with hemoglobin decreasing to less than 10 g/dL during treatment, and only Mac‐2 Binding Protein Glycosylation isomer (M2BpGi) (OR = 2.46; P  = 0.017) as an independent contributing factor associated with ALT non‐normalization after treatment. Cirrhotic patients may have a relatively high rate of treatment failure. In patients whose M2BpGi levels are elevated, their ALT tended to not normalize after treatment completion. These patients who did not achieve normalization of ALT after sofosbuvir plus RBV treatment need more careful observation for emergence of hepatocellular carcinoma even after achievement of SVR.